First report of structural characteristics and polymorphisms of the prion protein gene in raccoon dogs: The possibility of prion disease-resistance - Jo, Woo-Sung; Kim, Yong-Chan; Oem, Jae-Ku; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Prion diseases are fatal degenerative encephalopathies caused by misfolded prion protein (PrPSc) converted from normal prion protein (PrPC). Previous studies have reported that genetic polymorphisms of the prion protein gene (PRNP) play a critical role in susceptibility to prion diseases. In addition, prion disease-resistant animals showed unique structural features of prion protein (PrP) related to species-specific amino acids. However, investigations of genetic polymorphisms of the PRNP gene and structural characteristics of PrP have not been performed in raccoon dogs thus far. We investigated genetic polymorphisms of PRNP in 87 raccoon dogs using amplicon sequencing and analyzed the genotype, allele, haplotype frequencies, and linkage disequilibrium (LD) using Haploview version 4.2. In addition, we performed phylogenetic analysis and multiple sequence alignment (MSA) using MEGA X version 10.1.8 and Clustal X version 2.1, respectively. We estimated the impact of raccoon dog and Canidae family-specific amino acids using PolyPhen-2, PROVEAN, and AMYCO. Furthermore, we analyzed the effect of raccoon dog and Canidae family-specific amino acids using Swiss-PdbViewer program. We found 4 novel single nucleotide polymorphisms (SNPs) of the raccoon dog PRNP gene. In addition, the raccoon dog PrP showed 99.61% identity and the closest genetic distance to dog PrP. Among the substitutions of Canidae-specific amino acids with interspecific amino acids, D163N showed increased amyloidogenic propensity, and R181H showed alterations of hydrogen bonds. Furthermore, electrostatic potentials were changed according to the substitutions of D163N and R181H. By comparing PrP between raccoon dog and raccoon, R168K and K224R were found to be related to changes in hydrogen bonds, and K224R altered the electrostatic potential of raccoon dog PrP. To the best of our knowledge, this is the first study of genetic polymorphisms and structural features of the raccoon dog PRNP gene.